WHEN LANGUAGE BECOMES LAW: INDONESIAN JUDGES AND THE CHALLENGE OF BILINGUAL INTERNATIONAL CONTRACTS - Moh. Ali; Annisa Zerlina Cindy Gayatri (Faculty of Law, Universitas Diponegoro, 2026)
The regulation of contractual language has become a significant legal issue in Indonesia following the enactment of Article 31(1) of Law No. 24 of 2009, which requires Bahasa Indonesia, or the Indonesian language, to be used in agreements involving Indonesian parties. Although this provision was intended to affirm the legal status of the national language, its practical application has generated uncertainty, particularly due to inconsistent judicial interpretations concerning the validity of contracts drafted in foreign languages. This study examines the tension between linguistic formalism and the principle of freedom of contract as reflected in Articles 1320 and 1338 of the Indonesian Civil Code. Using a doctrinal legal research method supported by statutory, conceptual, case-based, and comparative approaches, this research analyses divergent judicial paradigms in several Indonesian court decisions. The Supreme Court in Decision No. 1572 K/Pdt/2015 and Decision No. 3395 K/Pdt/2019 adopted a strict formalistic approach by declaring foreign-language contracts null and void. Conversely, Decision No. 3415 K/Pdt/2021 and Amlapura District Court Decision No. 254/Pdt.G/2019/PN.Amp placed greater emphasis on substantive justice by recognising contractual validity based on consent, legal capacity, a specific subject matter, and a lawful cause. This article argues that Indonesian courts have inconsistently transformed an administrative language obligation into a substantive requirement for contractual validity, thereby weakening legal certainty and commercial predictability. Unlike previous studies that primarily addressed the legality of foreign-language contracts after the enactment of Law No. 24 of 2009, this research develops a broader analytical framework by examining judicial inconsistency through the theory of legal certainty, Economic Analysis of Law, and comparative contract law. It also positions contractual language regulation not merely as a technical drafting issue, but as a structural problem affecting investment predictability and transnational commercial stability. The comparative analysis of the Netherlands, Malaysia, and Singapore shows that these jurisdictions prioritise contractual intention and commercial practicality over linguistic rigidity. Accordingly, this study concludes that Indonesian contract law requires doctrinal reconstruction to reposition language as an evidentiary and administrative instrument rather than as a determinant of contractual validity.